موقع ودور محصول العدس في زراعة البقوليات الغذائية الجافة السورية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
يعد محصول العدس أحد أهم أنواع البقوليات الغذائية الجافة. ويرجع ذلك إلى مواصفاته البيولوجية والغذائية والاقتصادية الهامة من جهة وغناه بالعديد من العناصر الغذائية المعروفة بأهميتها. وتشير إحصائيات المنظمة العربية للتنمية الزراعية إلى أن سورية تشغل المرتبة الأولى بين الدول العربية في زراعة العدس، فقد بلغت المساحة المزروعة بهذا المحصول في الوطن العربي في عام 2007 نحو 213 ألف هكتار، زرع منها في سورية 150 ألف هكتار، أي ما يعادل 70% تقريباً من إجمالي مساحته في الدول العربية ولعدة سنوات، كما أن إنتاج القطر بلغ في نفس العام 109 ألف طن، وهو ما يعادل 71.4% من إجمالي إنتاجه في الوطن العربي. وتنتشر زراعة العدس في أغلب محافظات القطر، وتتركز بشكل أساسي في محافظات الحسكة وحلب وإدلب، حيث يزرع فيها ما يعادل 92% من إجمالي المساحة في القطر. وبشكل عام فإن للعدس أهمية كبيرة من الناحية الاقتصادية حيث يزرع في المناطق ذات التربة الفقيرة، ويتصف بضعف تأثره بالظروف الطبيعية المتغيرة، كما إنه يؤمن فائضاً مهماً للتصدير وسوف تزداد أهمية العدس في السنوات القادمة. Lentil is considered one of the most important kinds of dry legume because of its important biological, nutritional, and economic attributes on one hand and its richness with many important common components, on the other. According to the statistics of the Arab Organization for Agricultural Development, Syria occupies the first place in sowing lentil among all Arab countries. Lentil sowing area has reached about 213,0000 acres in 2007 in the Arab world. 150,000 acres have been sown in Syria, which nearly equals 70 % of the total area among the Arab countries and for many years. The Syrian production of lentil in the same year was (109,000) tons, which equals about 71.4 % of its total production in the Arab world. Sowing lentil spreads in most Syrian provinces. But it is basically centered in Al Hasaka, Aleppo, and Edleb where about 92 % of lentil is sown, compared to the total area of its production in Syria. In general, lentil occupies a great  economic importance as it can be sown in poor soil areas. It isn't affected by changeable natural conditions, and it provides an excessive amount  for exportation. Lentil's  importance will increase in the following years for it is a necessary and high-price food, both locally and internationally.